Alternate wetting and drying in Bangladesh: Water‐saving farming practice and the socioeconomic barriers to its adoption. (27th September 2018) - Pearson, Karen A.; Millar, Gearoid M.; Norton, Gareth J.; Price, Adam H.
Abstract: Water saving in irrigated agriculture is a critical issue for global food security, and much research has suggested substantial benefits of management systems designed to achieve it. Yet there are likely to be socioeconomic barriers which must be understood if these systems are to be adopted. Here, we highlight one example, Alternate Wetting and Drying (AWD) in Bangladesh. In Bangladesh, almost half of the workforce is engaged in agriculture and many people are dependent on rice as their staple food, sometimes consuming it three times per day. Rice production, therefore, is central both to economic well‐being and to food security in Bangladesh. However, this sector also faces a number of troubling problems. These include an electricity supply over‐stressed by irrigation pumps during the dry season, the gradual depletion of groundwater as a result of unsustainable use, the consumption of rice grains with elevated arsenic content, and the significant emission of rice‐based methane into the atmosphere. Interestingly, for more than a decade, evidence has indicated that AWD—an innovative farming practice—holds the promise of mitigating each of these threats to some degree and has been promoted by the Bangladeshi government. However, evidence seems to indicate that it has not been widely adopted in Bangladesh. This paper reviews the existing literature on AWD, related policies in Bangladesh, and the barriers to its uptake among farmers. The complicated relationship between agricultural and socioeconomic systems represents a key barrier to the successful use of AWD among Bangladeshi farmers. Similar barriers to water‐saving strategies are likely to exist in other countries and regions, and overcoming these barriers will be essential for AWD to be adopted. The case of Bangladesh provides important indications of how this might be achieved. Abstract : Alternative wetting and drying (AWD) is an irrigation scheduling technique being promoted in countries including Bangladesh that promises to reduce water and energy use in rice cultivation, while also reducing glasshouse gas emissions and rice grain arsenic content. Nonetheless, evidence suggests it is not being adopted by farmers. This paper reviews the rice agricultural system in Bangladesh and global AWD research before discussing the socioeconomic barriers to its adoption in Bangladesh.